The value of identification scanner technology in monitoring and detecting banned patrons in entertainment precincts. (9th December 2020) - de Andrade, Dominique; Puljević, Cheneal; Miller, Peter G.; Taylor, Nicholas; Curtis, Ashlee; Ferris, Jason
Abstract: Introduction and Aims: Networked identification (ID) scanner technology is a novel approach to collecting licensed venue attendance data, and potentially reducing alcohol‐related violence by detecting banned patrons. Using ID scanner data from three Queensland entertainment precincts (Safe Night Precincts; SNPs), we aim to: (i) examine patterns in patron attendance to licensed venues; and (ii) examine patterns in the detection of banned patrons. Design and Methods: We conducted descriptive analyses of licensed venue patron entries between 1 October 2017 and 30 June 2019. Scans during high alcohol hours (Friday and Saturday, 20:00–06:00) were stratified by patron sex and key age groups. We described scans associated with a detected banning notice issued by venues, courts or police across all Queensland SNPs and three key SNPs. Results: ID scanner data showed similar attendance trends across SNPs. The peak licensed venue entry hour was 23:00–23:59, with Saturday being the peak day. Approximately two‐thirds of scanned patrons were male, and patrons had a mean age of 25.8 years (SD = 8.80). Scanners detected 48 657 attempted entries by banned patrons, with the majority of attempts made by males (85%) aged 18–24 years (61%). Discussion and Conclusions: This study adds to the limited evidence on the use of ID scanners in the night‐time economy and highlights the feasibility of ID scanner use in this setting. Results demonstrate the value of scanners to passively collect data on patrons, identify banned patrons and assist in the enforcement of bans.